2014
DOI: 10.1007/s10897-014-9704-9
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Experiential Correlates of Public Attitudes Towards Cell‐Free Fetal DNA Screening

Abstract: This study seeks to inform clinical application of cell-free fetal DNA (cffDNA) screening as a novel method for prenatal trisomy detection by investigating public attitudes towards this technology and demographic and experiential characteristics related to these attitudes. Two versions of a 25-item survey assessing interest in cffDNA and existing first-trimester combined screening for either trisomy 13 and 18 or trisomy 21 were distributed among 3,164 members of the United States public. Logistic regression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Additionally, the distributions of respondent age (lower) (χ 2 [5, N=3164]=166.340, p <0.001); household income (higher) (χ 2 [4, N=3164]=140.058, p <0.001); and educational attainment (higher) (χ 2 [4, N=3164]=469.694, p <0.001) were significantly different from those of the national population. Additional demographic information, such as experience with parenting or disability, and their correlates with testing recommendations, is reported elsewhere (Sayres et al 2014). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the distributions of respondent age (lower) (χ 2 [5, N=3164]=166.340, p <0.001); household income (higher) (χ 2 [4, N=3164]=140.058, p <0.001); and educational attainment (higher) (χ 2 [4, N=3164]=469.694, p <0.001) were significantly different from those of the national population. Additional demographic information, such as experience with parenting or disability, and their correlates with testing recommendations, is reported elsewhere (Sayres et al 2014). …”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant differences in the frequency of any of these codes were detected between responses to the trisomy 13/18 and trisomy 21 surveys. Because many respondents did not make a clear choice for or against NIPT (see Sayres et al 2014), and many reasons cited for respondents’ choices referred to prenatal testing generally rather than any particular technology, we have presented this qualitative analysis by code only, rather than by test recommendation. However, where relevant, we have noted the relationship between these themes and specific recommendations for or against NIPT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous public opinion studies have found support in the United States (US) for the hypothetical availability of cfDNA screening (Allyse, Sayres, Goodspeed, Michie, & Cho, 2015; Allyse, Sayres, Goodspeed, & Cho, 2014), especially among populations with higher education and income levels (Sayres, Allyse, Goodspeed, & Cho, 2014). Farrell et al have conducted focus groups with small numbers of English-speaking pregnant women and also found general support, tempered with concerns around maintaining patient autonomy and clarity in results and their implications (Farrell, Mercer, Agatisa, Smith, & Philipson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study in California found that 35% of Latinas with elevated risk pregnancies accepted the offer of cfDNA screening; women who scored higher on a knowledge scale (who were also more often fluent in English) more often accepted cfDNA screening, and most women who refused cfDNA also refused invasive testing (Farrell, Hawkins, Barragan, Hudgins, & Taylor, 2015). A recent national survey showed no significant difference in interest in cfDNA screening among those who identify as Latino/a and those who do not, although the survey was conducted only in English (Sayres et al, 2014). No studies to date have compared the in-depth views of Latina and non-Latina pregnant women on cfDNA screening.…”
Section: Introductionmentioning
confidence: 99%